Research progress on microbial adsorption of radioactive nuclides in deep geological environments - Wang, Tianyu; Zhang, Qichao; Qiao, Yanxin; Jiang, Yishan; Xiao, Feng; Duan, Jizhou; Zhao, Xin (Frontiers in Microbiology, 2024)
Due to the development and utilization of nuclear energy, the safe disposal of nuclear waste needs to be urgently addressed. In recent years, the utilization of microorganisms' adsorption capacity to dispose of radioactive waste has received increasing attention. When compared with conventional disposal methods, microbial adsorption exhibits the characteristics of high efficiency, low cost, and no secondary pollution. In the long term, microbial biomass shows significant promise as specific chemical-binding agents. Optimization of biosorption conditions, identification of rare earth element binding sites, and studies on the sorption capacities of immobilized cells provide compelling reasons to consider biosorption for industrial applications in heavy metal removal from solutions. However, the interaction mechanism between microorganisms and radioactive nuclides is very complex. This mini-review briefly provides an overview of the preparation methods, factors affecting the adsorption capacity, and the mechanisms of microbial adsorbents.